1998
DOI: 10.1021/ja981651m
|View full text |Cite
|
Sign up to set email alerts
|

The C4H6•+ Potential Energy Surface. 1. The Ring-Opening Reaction of Cyclobutene Radical Cation and Related Rearrangements

Abstract: Ab initio MO and density functional calculations indicate that the ring opening of the cyclobutene radical cation (CB •+) follows two competitive pathways, whose energy barriers differ by less than 1 kcal/mol at the highest level of theory employed, RCCSD(T)/cc-pVTZ//UQCISD/6-31G*. The first corresponds to a conrotatory rearrangement to the cis-butadiene radical cation (cis-BD •+). The second one leads to trans-BD •+ via a very flat potential energy plateau which comprises cyclopropylcarbinyl-type structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(97 citation statements)
references
References 44 publications
(62 reference statements)
6
90
1
Order By: Relevance
“…9) is the most stable form of the ion [40][41][42][43] and of the neutral [20]. The predominant dissociation pathway is seen to be C 2 + C 2 with C 4 being twice as likely.…”
Section: H 6 +mentioning
confidence: 99%
“…9) is the most stable form of the ion [40][41][42][43] and of the neutral [20]. The predominant dissociation pathway is seen to be C 2 + C 2 with C 4 being twice as likely.…”
Section: H 6 +mentioning
confidence: 99%
“…11. [14] On the right hand side of this Figure one can see that, if the radical cation of cyclobutene (CB •+ ) undergoes electrocyclic ring-opening to cis-BD •+ in the con-or disrotatory fashion, while an axis or a plane of symmetry is retained, respectively, the ground states of the two compounds invariably correlate with excited states of the products. Thus the systems evolve towards conical intersections which are avoided by vibronic coupling which breaks the remaining symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…The Ring Opening of the Cyclobutene Radical Cation (CB •+ ) [14] During the first years of chemistry we learn that the ring-opening of cyclobutene is a textbook example for the operation of the Woodward-Hoffman rules for electrocyclic reactions. We wanted to investigate whether similar rules can also be applied to radical cations, but we found that this is not the case, because ionization of CB in Ar matrices led directly to the trans isomer of the butadiene radical cation (BD •+ ), while no trace of the cis-isomer was ever seen.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the symmetry preserving pathway is subject to Jahn-Teller distortions that increase the activation energy even more. 28,36 The overall result is an acceleration of slow or symmetry forbidden cycloadditions, [37][38][39] electrocyclic reactions, [40][41][42][43][44][45] sigmatropic shifts, [46][47][48] An explanation for the increased reaction rates observed for radical cation Diels-Alder reactions has been proposed by Bauld and is shown in Scheme 4.1. 51 The same principle is applicable for other radical cation pericyclic reactions.…”
Section: Mechanism and The Origin Of The Rate Accelerationmentioning
confidence: 99%